The last trial - Turow, Scott (Grand Central Publishing, 2020)
"At 85 years old, Alejandro "Sandy" Stern, a brilliant defense lawyer with his health failing but spirit intact, is on the brink of retirement. But when his old friend Dr. Kiril Pafko, a former Nobel Prize winner in Medicine, is faced with charges of insider trading, fraud, and murder, his entire life's work is put in jeopardy, and Stern decides to take on one last trial. In a case that will provide the defining coda to both men's accomplished lives, Stern probes beneath the surface of his friend's dazzling veneer as a distinguished cancer researcher. As the trial progresses, Stern will question everything he thought he knew about his friend. Despite Pafko's many failings, is he innocent of the terrible charges laid against him? How far will Stern go to save his friend, and-no matter the trial's outcome-will he ever know the truth? Stern's duty to defend his client and his belief in the power of the judicial system both face a final, terrible test in the courtroom, where the evidence and reality are sometimes worlds apart"--